REGIONALIZATION CHALLENGES AND ECONOMIC DEVELOPMENT IN PERU - López Más, Johans Julio (2014)
The regionalization process, aim the formation of transverse macro-regions. This new vision of development means a reunion with the region’s potential to reduce economic and social inequalities gaps. Interregional Coordination Meetings (ICM) (Internor, South Central, Amazon, Macrosur) are voluntary groupings among regional governments were able to identify a set of articulators projects (28 projects), which would promote physical integration and enterprises for local economic development. In addition, the ICM, in joint action with the Regional Development Agencies Private Investment, would generate future sustainable conditions to form regions. To this end, we must make changes to the Public Investment Policy of the Ministry of Economy and Finance (MEF), and also make changes in the regulations of decentralization to create execution units in ICM, with development agendas of short and medium term planning units and programs adequately funded multi-year investment.